Myth America : historians take on the biggest legends and lies about our past - Kruse, Kevin Michael, 1972-; Zelizer, Julian E. (Basic Books, 2022)
"The United States is in the grip of a crisis of bad history. Inaccurate interpretations and outright misrepresentations of the past--cultivated within and promoted by the conservative movement and right-wing media over the last several decades-hold sway among large numbers of Americans, damaging our public discourse. In Myth America, historians Kevin Kruse and Julian Zelizer have assembled an all-star team of historians to provide textured analysis that explains what we get wrong about the past. Drawing on their immense knowledge of scholarship and their own primary research, these contributors provide correctives to the ways conservatives distort history to serve the needs of their anti-democratic agenda. For instance: Erika Lee shows how, far from posing a relentless threat to America, immigrants have long been recruited and even coerced to come to the United States. Joshua Zeitz traces how the welfare programs of the Great Society, criticized by the right as wasteful failures, have provided millions of Americans with food security, health care, and education. Carol Anderson uncovers how racism and anxiety over the nation's changing demographics, not voter fraud, are motivating Republicans' assault on voting rights. Elizabeth Hinton reveals that, rather than curbing crime, patrolling low-income communities with outside police forces has historically intensified violence and made everyone less safe. Taken together, the essays unveil how corporate interests and right-wing politicians use bad history to fan the flames of white resentment and unravel America's social safety net. Replacing myths with research and reality, Myth America is essential reading amid today's heated debates about our nation's past"--